Spatially-defined motor deficits in people with unilateral complex regional pain syndrome. (July 2018) - Reid, Emily J.; Braithwaite, Felicity A.; Wallwork, Sarah B.; Harvie, Daniel; Chalmers, K. Jane; Spence, Charles; Gallace, Alberto; Moseley, G. Lorimer
Abstract: Objective: Spatially-defined disruption of autonomic and sensory function has been identified in Complex Regional Pain Syndrome (CRPS). This study aimed to determine whether motor performance is also disrupted in a spatially-defined manner in people with CRPS. Methods: Thirteen people with CRPS type 1 of the upper limb participated in two motor experiments. In Experiment 1 participants performed a circle drawing task that primarily tested motor accuracy. In Experiment 2 participants performed a button pressing task that tested motor co-ordination. In both experiments the motor tasks were performed with either hand (affected or healthy), and on either side of the body midline – that is, on the affected side of space or healthy side of space. Results: There was a main effect of both Limb and Side for the motor tasks. In Experiment 1, motor accuracy for the circle drawing task was poorer when participants used their affected hand than when they used their healthy one ( p < .001), and when the task was performed on the affected side of their body midline than when it was performed on the healthy side ( p < .001). In Experiment 2, motor co-ordination for the button pressing task was poorer when participants used their affected hand than when they used their healthy one ( p < .001), and when the task was performed on the affected side of the midline ( p < .001), as compared to the healthy side of the midline. Conclusions: Unilateral CRPS is associated with a spatially-defined disruption of motor performance. Participants perform worse when the task is performed on the affected side of the body midline, regardless of whether they use their affected or healthy hand.